PRODUCTIVITY, REPEATABILITY OF PRODUCTIVE AND REPRODUCTIVE TRAITS OF LOCAL PIGEON - Darwati, S.; Martojo, H.; Sumantri, C.; Sihombing, D.T.H.; Mardiastuti, A. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
The purpose of this study was to know productivity and repeatability of local pigeon. Data werecollected from 124 birds that reared under intensive management. The results showed that artificial pairwas 100% and polygamy was 16% (n=62 pair of pigeon). The ration of local pigeon consisting of 50%corn+50% of commercial feed for starter broiler chicken can be applied in field. The average of eggproduction was 1.8 eggs/pair/period, egg weight was 17.7 g, fertility was 96.6%, hatching rate was 77%,embryo mortality rate was 23%, interval period from laying to hatching and suckling was 51 days, 31.4days with hatching, and 17.6 days without hatching and suckling. The day old pigeon weight ranged10.9-16.2 g. Repeatability value of productive traits was high, in which egg weight was 0.64 and day oldpigeon weight was 0.737. Repeatability of reproductive traits was low, that was fertility and hatchabilitywas 0.12 and 0.048, respectively). The squab weight increased from week 0 to 4, then decreased in theweek 5. The growth rate was highest at the week 1, then decreased from the week 2 to 5 with thenegative growth rate occur at the 5th week. The squab growth rate followed a quadratic pattern. It wasconcluded that slaughter squab selection could be done at 4th week old.